2023
DOI: 10.3390/plants12203544
|View full text |Cite
|
Sign up to set email alerts
|

Species Delimitation and Genetic Relationship of Castanopsis hainanensis and Castanopsis wenchangensis (Fagaceae)

Xing Chen,
Yi Feng,
Shuang Chen
et al.

Abstract: Castanopsis is one of the most common genus of trees in subtropical evergreen broad-leaved forests and tropical monsoon rainforests in China. Castanopsis hainanensis and Castanopsis wenchangensis are endemic to Hainan Island, but they were once confused as the same species due to very similar morphologies. In this study, nuclear microsatellite markers and chloroplast genomes were used to delimit C. hainanensis and C. wenchangensis. The allelic variations of nuclear microsatellites revealed that C. hainanensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Previous studies also suggested that genetic introgression and hybridization happened between some closely related Castanopsis species (Chen et al. 2023 ). The synonymous substitution rate of nuclear genomes in plants has been reported to evolve two times faster than that of chloroplast genomes (Wolfe et al.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies also suggested that genetic introgression and hybridization happened between some closely related Castanopsis species (Chen et al. 2023 ). The synonymous substitution rate of nuclear genomes in plants has been reported to evolve two times faster than that of chloroplast genomes (Wolfe et al.…”
Section: Discussionmentioning
confidence: 89%
“… 2023 ); KT793041 (Hinsinger and Strijk 2017 ); OR545365 (Chen et al. 2023 ); ON710842 (unpublished); MZ433364 (unpublished); MW043480 (Peng et al. 2021 ); MK571045 (Ye et al.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it has become common to use DNA variation data to study population structure and genetic differentiation. Simple sequence repeat (SSR) is a commonly used molecular marker and has been widely used to investigate genetic diversity, for example in assessing the population structure and conservation units of Castanopsis sclerophylla [ 23 ] and species delimitation between Castanopsis hainanensis and Castanopsis wenchangensis [ 24 ]. Thus far, the genetic differentiation and relationship among C. chinensis , C. glabrifolia , and C. qiongbeiensis have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%